Official Sanctity alla Veneziana: Gerardo, Pietro Orseolo and Giacomo Salomani - Karen McCluskey (Conserveries Mémorielles)
Throughout late-medieval and Renaissance Italy, pious men and women were recognized as saints during their own lifetime and accorded at least local veneration at the site of their tomb after death. Despite the absence of formal canonisation, such cults were often promoted by local governments keen to enlist the beati as potent new intercessors and protectors for their native towns. The situation in late-mediaeval Venice appears to be quite different. Despite the existence of an abundance of religious cults in Venice, in the 13th and 14th centuries only three local beati attained official recognition by the Republic: the bishop and martyr Gerardo da Venezia (d. 1046); the doge Pietro Orseolo (d. 976), and the Domincan friar Giacomo Salomani (d. 1314). This essay examines their state-sponsored imagery, in San Marco and elsewhere, to shed light on the reasons why these three Venetian holy men were singled out as worthy of attention by their government. This analysis goes some way to understanding the unique devotional tradition rehearsed in the city of Venice, specifically in relation to the city’s contingent of local holy men and women.